Kebijakan Dividen Ditinjau Dari Kinerja Total Asset Turn Over, Current Ratio, Debt To Equity Ratio Dan Return On Assets - Riza Vebriyanti; Elen Puspitasari (Owner : Riset dan Jurnal Akuntansi, 2023)
Indonesian companies carry out a dividend policy with investors by dividing dividends annually, but the company retains it in the form of profit to be used as investment financing in the future. This study aims to test and analyze by finding empirical evidence about the effect of total asset turnover, current ratio, debt to equity ratio, and return on assets  on dividend policy in companies listed on the Indonesian Stock Exchange in 2018-2021. Dividend policy is a decision to share profits earned by the company to shareholders as dividends, or to retain them in the form of retained earnings to be used as investment financing in the future. This type of research is classified as a quantitative type and uses secondary data from www.idx.co.id. The number of samples produced by purposive sampling were 76 companies according to the criteria multiplied by 4 years of the manufacturing company period. Multiple linear regression is the hypothesis test used in this study. The results of this study were that the total asset turnover and return on assets had a positive effect on dividend policy, but the current ratio and debt-to-equity ratio variables had no effect on dividend policy.